241 Clinical outcomes of metastatic melanoma patients with liver metastases treated with anti-PD-1 monotherapy versus combination ipilimumab/nivolumab. (9th November 2020) - Ma, Vincent; Griffith, Kent; Waninger, Jessica; Daignault-Newton, Stephanie; Fecher, Leslie; Alva, Ajjai; Lao, Christopher
Abstract : Background: Recent studies report of liver metastases (LM) as a poor prognostic factor in patients treated with immune checkpoint inhibitors (ICIs), 1 but clinical outcomes associated with different ICI regimens remains uncertain. In this study, we investigate melanoma patients with and without LM and assess differential treatment outcomes associated with anti-PD-1 monotherapy and combination ipilimumab/nivolumab (I/N). Methods: We conducted a single-center, retrospective review of advanced stage melanoma patients with and without LM treated with anti-PD-1 monotherapy (nivolumab or pembrolizumab) or I/N between 2012 and 2018. Overall survival (OS) and progression free survival (PFS) were measured from the first dose of treatment to date of death and clinical or radiographic progression, respectively. Univariate and multivariate analysis were performed using Cox proportional hazard (CPH) models and logistic regression models. Inverse probability of treatment weighting using propensity scores in CPH models was used to account for the following baseline covariates: age, ECOG performance status, BRAF status, pre-treatment LDH level, prior therapy status, and number and sites of metastases. Results: 327 patients were identified, 87 with LM and 240 without LM. Patients with LM was associated with worse PFS [HR: 2.1, 95% CI, 1.5 – 3.1] (figure 1) and OS [HR: 3.4, 95% CI, 2.2 – 5.2] (figure 2). Respective 3-year PFS and OS estimates associated with anti-PD-1 monotherapy were 21.8% and 28.7% in patients with LM (figure 3, figure 4); and 36.5% and 57.6% without LM (figure 5, figure 6). Respective 3-year PFS and OS estimates associated with I/N were 46.7% and 56.7% in patients with LM; and 58.0% and 74.4% without LM. Conclusions: In melanoma patients treated with PD-1 inhibitor-based regimens, the presence of LM leads to poorer survival outcomes. Our study suggests the poor prognosis associated with LM can be substantially mitigated by treatment with combination I/N over anti-PD-1 monotherapy. Further studies are warranted to investigate the anti-immunotherapy effect associated with LM. Ethics Approval: The study was approved by the University of Michigan institutional ethical guidelines and patients' consents were waived following Institutional Review Board protocol review (HUM00156014). Reference: Bilen MA, Shabto JM, Martini DJ, et al. Sites of metastasis and association with clinical outcome in advanced stage cancer patients treated with immunotherapy. BMC Cancer 2019; 19(1):857.